The correlation between gene expression of growth differentiation factor 9B (GDF9B) gene and miR-378-5p in infertile women - Al-Kafagi, Hiba Muneer Abd-Alhassan; Abdul Hussein, Noor Nihad; Mohammed, Maryam Qasim; Hussein, Zaid Ali; Al-Tameemi, Ahlam Khaleefah Abdal (Iraqi Journal of Science, 2025)
The normal expression of follicle-producing genes, hormone balance, and reproductive physiology all have a significant impact on female fertility. Infertile Iraqi women were compared to controls who appeared to be in good health in order to assess the gene expression of the GDF9B gene. The second goal is to quantify the gene expression of a particular miRNA, such as miRNA 378-5p, that specifically targets the GDF9B gene. In addition to 50 samples from female patients, the study also used 50 samples from the control group. The ELISA technique was used to measure the levels of the hormones FSH, LH, AMH, and prolactin. Also, real-time qPCR was used to measure the gene expression of the GDF9B gene and the miRNA 378-5p gene that it targets. The results showed an increase in the level of hormones in patients in both groups compared with healthy females, with highly significant differences, while there was a decrease in the level of gene expression of the GDF9B gene in patients compared with healthy subjects, by folds 0.2 and 0.3, as well as an increase in the gene expression of miRNA 378-5p in patients compared with healthy subjects. The considerations that female fertility is strongly influenced by reproductive physiology, hormonal balance, and efficient follicle-forming gene expression led us to the conclusion that the relevance of the GDF9B gene and its function in ovarian development are confirmed by the lower expression of the gene in infertile women. Moreover, a high level of miRNA 378-5p suggests that the expression of genes is being controlled post-transcriptionally and that the gene’s function is being restricted. Hence, it’s possible that a patient’s excessive hormone levels are linked to ovaries that have abnormalities, which interfere with reproduction.